2016
DOI: 10.1155/2016/7692024
|View full text |Cite
|
Sign up to set email alerts
|

T Helper Cell Subsets in Clinical Manifestations of Psoriasis

Abstract: Psoriasis is a chronic inflammatory skin disease, which is associated with systemic inflammation and comorbidities, such as psoriatic arthritis and cardiovascular diseases. The autoimmune nature of psoriasis has been established only recently, conferring a central role to epidermal CD8 T cells recognizing self-epitopes in the initial phase of the disease. Different subsets of helper cells have also been reported as key players in the psoriasis pathogenesis. Here, we reviewed the knowledge on the role of each s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
80
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(87 citation statements)
references
References 77 publications
4
80
0
3
Order By: Relevance
“…One panel was used to confirm the Th cell lineages using 7 immunofluorescent markers. The results confirmed the increased proportion of Th1 and Th17 cells ( Figure 6A), which had been reported before (8). We further discovered that Tfh, Tc1, and Tc17 cell numbers were significantly elevated in samples for patients with PS compared with those in samples from the HC group.…”
Section: Expression Levels Of 24 Immune Markers On the Major Immune Csupporting
confidence: 91%
See 1 more Smart Citation
“…One panel was used to confirm the Th cell lineages using 7 immunofluorescent markers. The results confirmed the increased proportion of Th1 and Th17 cells ( Figure 6A), which had been reported before (8). We further discovered that Tfh, Tc1, and Tc17 cell numbers were significantly elevated in samples for patients with PS compared with those in samples from the HC group.…”
Section: Expression Levels Of 24 Immune Markers On the Major Immune Csupporting
confidence: 91%
“…Despite these encouraging results, clinical outcomes remain highly variable, providing evidence that PS is a systemic and heterogeneous disease and highlighting the requirement to deepen our current understanding of the disease (7). Different subsets of Th cells have been reported to contribute to the pathogenesis of PS (1,8,9), such as Th1, Th9, Th17, and Th22 cells, whereas other contributors are skin-homing memory T cells (1) or Tregs (10). Therefore, complicated immune dysregulation may result in alterations in the frequency, function, or location of any one of these Th or T cytotoxic (Tc) subpopulations, which determine the severity of different pathologies (11,12).…”
Section: Introductionmentioning
confidence: 99%
“…Despite having a crucial role in the immunity against pathogens, helper T cells are also involved in immune system-related diseases, including allergies and autoimmune pathologies. It is well established that Th2 responses mediate allergy and, currently, major efforts are directed to understand the pathological balance of Th1, Th2, and Th17 polarisation in autoimmune diseases [14]. …”
Section: Introductionmentioning
confidence: 99%
“…Deciphering the function and clinical relevance of pathogenic T cells in psoriasis is critical for understanding how they affect the development and course of disease [15,16]. In the present study, we found that a subpopulation of CD3 1 CD20 1 T cells were characterized as activated effector cells in the peripheral blood of patients with psoriasis, and these cells produced high levels of proinflammatory cytokines that correlated with disease severity, implying that CD3 1 CD20 1 T cells might play a role in T cellmediated pathogenic immune response of psoriasis.…”
Section: Discussionmentioning
confidence: 99%